Pemanfaatan Agregat Sungai Messawa Kabupaten Mamasa Dalam Campuran AC-BC - Roinaldy Sangle; Alpius; Ari Kusuma (Paulus Civil Engineering Journal, 2022)
Aggregate is one of the most needed mixed materials in a pavement layer, therefore aggregate before being used in road pavement mixtures must be examined first for its characteristics, especially in mixed AC-BC concrete. Examination/testing of characteristics is carried out using the Conventional Marshall method based on the General Specifications of Highways 2018, the purpose of the test is to obtain an KAO value, then a test object is made for KAO to obtain a Residual Marshall Stability value. And the results of inspection/testing of the aggregate originating from the Messawa River, Mamasa Regency have met the specified standard specification requirements, that it can be used in the AC-BC mixture. Based on the Conventional Marshall test the Stability, VIM, Flow, VMA and VFB values obtained have met the specification standards. For the Marshall Immersion inspection, the value obtained was 95.24% with an asphalt content of 6%, where this value met the 2018 General Highways Specifications standard